Claudin‐4 binder C‐CPE 194 enhances effects of anticancer agents on pancreatic cancer cell lines via a MAPK pathway. Issue 6 (20th December 2015) - Kono, Tsuyoshi; Kondoh, Masuo; Kyuno, Daisuke; Ito, Tatsuya; Kimura, Yasutoshi; Imamura, Masafumi; Kohno, Takayuki; Konno, Takumi; Furuhata, Tomohisa; Sawada, Norimasa; Hirata, Koichi; Kojima, Takashi
Abstract: The C‐terminal fragment of Clostridium perfringens enterotoxin (C‐CPE) modulates the tight junction protein claudin and disrupts the tight junctional barrier. It also can enhance the effectiveness of anticancer agents. However, the detailed mechanisms of the effects of C‐CPE remain unclear in both normal and cancerous cells. The C‐CPE mutant called C‐CPE 194 binds only to claudin‐4, but the C‐CPE 194 mutant called C‐CPE m19 binds not only to claudin‐4 but also to claudin‐1. In the present study, to investigate the mechanisms of the effects of C‐CPE on claudin expression, the tight junctional functions and the cytotoxicity of anticancer agents, human pancreatic cancer cells, and normal human pancreatic duct epithelial cells (HPDEs) were treated with C‐CPE 194 and C‐CPE m19. In well‐differentiated cells of the pancreatic cancer cell line HPAC, C‐CPE 194 and C‐CPE m19 disrupted both the barrier and fence functions without changes in expression of claudin‐1 and ‐4, together with an increase of MAPK phosphorylation. C‐CPE 194, but not C‐CPE m19, enhanced the cytotoxicity of the anticancer agents gemcitabine and S‐1. In poorly differentiated pancreatic cancer cell line PANC‐1, C‐CPE 194, but not C‐CPE m19, decreased claudin‐4 expression and enhanced MAPK activity and the cytotoxicity of the anticancer agents. In normal HPDEs, C‐CPE 194 and C‐CPE m19 decreased claudin‐4 expression and enhanced the MAPK activity, whereas they did not affect the cytotoxicity of the anticancer agents. Our findings suggest that the claudin‐4 binder C‐CPE 194 enhances effects of anticancer agents on pancreatic cancer cell lines via a MAPK pathway.